The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1751-1097.1998.tb03249.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Solvatochromism of Neutral Red

Abstract: Abstract— The effect of solvent polarity on the electronic absorption and fluorescence properties of neutral red (NR), a phenazine‐based dye of biological importance has been investigated in several neat and mixed solvents. An unusual dual solvatochromic behavior has been observed that reveals the existence of two closely spaced electronic excited states in NR. In low‐polarity solvents the fluorescence of the NR is mainly emitted from the localized excited state, whereas in high‐polarity solvents the emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 23 publications
8
98
0
Order By: Relevance
“…As reported by Han et al, 15 the fluorescence radiative decay rate constants, k r , of PTZ-5 are almost the same in all solvents, but the nonradiative decay constants, k nr , decrease severely from protic solvents to aprotic solvents. According to the discussion on C151 and neutral red, 3,4 it is reasonable to suppose that the emission state of PTZ-5 is always ππ* in all solvents and that the fluorescence quantum yields are modulated by changing the nonradiative decay rate such as C151.…”
Section: à32mentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by Han et al, 15 the fluorescence radiative decay rate constants, k r , of PTZ-5 are almost the same in all solvents, but the nonradiative decay constants, k nr , decrease severely from protic solvents to aprotic solvents. According to the discussion on C151 and neutral red, 3,4 it is reasonable to suppose that the emission state of PTZ-5 is always ππ* in all solvents and that the fluorescence quantum yields are modulated by changing the nonradiative decay rate such as C151.…”
Section: à32mentioning
confidence: 99%
“…The fluorescence properties of C151 and neutral red in protic solvents are also affected by specific solvent effects. 3,4 Excitedstate proton transfer (ESPT) is considered a very important reaction in the excited-state dynamics of fluorophore.…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies indicated that they would interact directly with biocompounds such DNA bases via photoinduced electron transfer. 6 On the other hand, PZ derivatives can present appreciable fluorescence [7][8][9][10] enabling their specific use as fluorescent probes in biological environment, where small quantities are enough to be detected without disturbing the system in study. Some PZ derivatives can also present steady-state phosphorescence, relatively weak but observable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The acid-dissociation constant (K a ) for NR was reported to be 10 -6.8 [12]. Therefore, NR changes to its cationic form (HR + ) under acidic conditions and it shows an attractive interaction with anionic AOT, whereas it changes to its nonionic form, which has a weak interaction with AOT, under alkaline conditions.…”
Section: Effect Of the Nacl Concentration On The Neutral Red Extractionmentioning
confidence: 99%